TINGKAT PERUBAHAN KESEJAHTERAAN EKONOMI KELUARGA BURUH MIGRAN: DI DESA PANGGUNGREJO GONDANGLEGI MALANG - Babun Ni’matur Rohmah; Riska Ayu Purnama Sari (LP3M IAI Al-Qolam, 2017)
Gondanglegi sub district is occupying the first position as the largest supplier of migrant workers in the area of ​​South Malang in 2014. This research focuses on Panggungrejo Village as the object of research. A village with area of ​​203 km2, population of 1,877 people consisting of 866 men and 1,011 women. This village pervades 12 RTs, and this research took 2 RTs namely RT 5 and 6, with 5 respondents. These five respondents are representatives of various migrant workers. Some represent their wives as migrant workers, husbands and children. This study uses the theory of social mobility; a change, shift, increase or decrease of the status and role of its members. Welfare indicators used are economic, educational, social and health. The result of the research shows that there is a change of the respondents’ life level in terms of economic, social, educational and even health compared to prior becoming migrant worker, although the rate of change is not too significant. Keywords: Welfare, Migrant Worker, Social Mobility.